Synthesis of Zinc oxide nanorods via conductive polymeric template and its potential application in hybrid solar cells. - Pourjafari Nokandeh, Dena (2014)
Finally my Ph.D project arrived at its final point. During these three years I have learned and experienced a lot of things in my life, from the first day when I arrived to Mexico till today that I am writing these final pages. I remember when I arrived to Mexico, I didn’t know Spanish, except some words. Everything was different from my country like the language, the weather, the culture and the FOOD. I had to learn Spanish to be able to communicate with people and manage my life. I had to learn how to eat spicy food, sweating and enjoy my meal!! It was not easy at all but it was all fun since I was in many funny situations learning Spanish!